Electromechanical interrelations during dobutamine stress in normal subjects and patients with coronary artery disease: comparison of changes in activation and inotropic state. Issue 4 (1st April 2001) - Duncan, A M; O'Sullivan, C A; Gibson, D G; Henein, M Y
Abstract : OBJECTIVE: To identify the effects of altered ventricular activation during dobutamine stress on left ventricular function in normal subjects and in patients with coronary artery disease, and to distinguish these from an inotropic response. DESIGN: Prospective analysis of 12 lead ECG and echocardiogram at rest and at peak stress. SETTING: Tertiary referral centre for cardiac disease equipped with non-invasive facilities for pharmacological stress testing. METHODS: 22 patients with coronary artery disease were compared with 17 age matched controls. Left ventricular ejection and filling patterns were assessed using Doppler echocardiography. Activation effects were correlated with relative left ventricular ejection and filling times, and the Z ratio ([left ventricular ejection + filling times]/RR interval). Inotropic response was measured from peak aortic acceleration. RESULTS: In controls, QRS shortened (by 4 ms, p < 0.001), and total ejection and filling periods lengthened (by 2 s/min, p < 0.01 and 5 s/min, p < 0.001, respectively). The Z ratio thus increased and correlated with QRS shortening ( r 2  = 0.69). Peak aortic acceleration (PAA) increased by 135%, p < 0.001. In patients, QRS lengthened at peak stress (by 9 ms, p < 0.001). Total ejection and filling times did not change, but Z ratio fell, correlating with QRS prolongation ( r 2  = 0.65). Nevertheless, PAA increased by 63%, p < 0.001. CONCLUSIONS: Relative ejection and filling times reflect ventricular activation at rest and during stress independent of changes in inotropic state. By contrast, peak aortic acceleration reflects the positive inotropic effect of dobutamine on the myocardium, regardless of changes in activation.